PENGGUNAAN MEDIA PENGAJARAN (ALAT PERAGA) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 009 TEMBILAHAN KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Indraleka (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low results of fifth grade students learn math SD Negeri 009 Tembilahan Of the 30 students, only 12 students who completed study results. In addition the average student learning outcomes is equal to 58.83. Cause of low learning outcomes are: (a) the students are very noisy when teachers convey instructional materials; (b) the lack of attention and seriousness of students in the process of learning activities; (c) students do not respond to the learning of teachers; (d) students feel bored follow the learning process; and (e) students are not interested in these subjects. For that conducted research with the aim to improve students' mathematics learning outcomes through the medium of instruction (props). This research is a class act who performed as much as two cycles consisting of two meetings. The subjects were fifth grade students of SD Negeri 009 Tembilahan totaling 30 students. Data collection techniques used in this study was the observation techniques and test engineering. The data used in this study focuses on the data increase students 'mathematics learning outcomes, while analysis is done is descriptive analysis of the results of students' mathematics learning. Based on the survey results revealed that the learning outcomes have increased in each cycle. This is evidenced by the acquisition of student learning outcomes, on the basis of an average score of learning outcomes at 58.83 with the number of students who completed 18 students, the first cycle average of 66.97 students' learning outcomes with the number of students who completed 24 students, and the second cycle average of 78.16 students' learning outcomes with the number of students who completed 30 students.